Performance Measurement ERP System Module Purchase and Sale Cooperation on Consumption in Tangerang District - Hendra Alianto (International Journal of Informatics and Communication Technology (IJ-ICT), 2016)
ERP system is an integrated information system to support the core business activities of an organization, helping the business unit related to data and information sharing, cost reduction, and improvement of business processes, which will have an impact on the increase in the work to become more efficient and effective. Organizations that implement ERP system can take the form of cooperative consumption. Purpose cooperative consumption implement an ERP system is to achieve improved productivity and operational effectiveness of the cooperative. Standard Operating Procedures can help the user can use the ERP system, but required knowledge management. This rapid business development prosecute organizations innovate to maintain and grow the business. One such effort is the one measuring the performance achieved are supported by the implementation of the Knowledge Management. In this information age, where information must be obtained relatively quickly, accurately and easily without being limited by space, time, location.The important thing is how to measure the performance of the ERP system once implemented. Performance measurement module ERP system purchases and sales on consumer cooperatives, will give inputandan innovation for consumer cooperatives in developing the organization towards a more structured, competitive and advanced, and improve decision making, increase the efficiency of operations and business processes.Keywords:  ERP Systems, Knowledge Management, Purchase and Sales Modules